Comparative politics and government - Palekar, S. A. (New Delhi, 2009)
This well-organized and systematic study takes into account these developments and shift in approach in the field of comparative government and politics. As the empirical study of political processes, structures and functions forms a major part of comparative political studies, the author examines them in detail. He also analyzes the many variables that are heterogeneous in nature. The book analyzes in tandem comparative government which involves the study of different political systems with their institutions and functions and comparative politics, which covers comparative governments and non-state politics. The latter also studies rule making, rule implementing and rule adjudicating. Since different political systems are governed by the constitutions of the nations concerned, the book deals in detail with the constitutions of these countries. While the text gives a comprehensive coverage of constitutions of democracies such as UK, USA, France, Switzerland and Japan, it also deals with the constitutions of authoritarian States like Russia and China. This text should be of great value to undergraduate and postgraduate students of political science as well as aspirants of civil services.
Keywords: Political Science